DIGITAL ECOSYSTEMS AS A DRIVER OF BUSINESS LANDSCAPE TRANSFORMATION IN THE MODERN ECONOMY - Ganna Kolomiyets; Vladуslav Korol; Dmуtro Bilіanskiy (Baltic Journal of Economic Studies)
The article defines the features of the ecosystem business model, reveals the importance and role of digital ecosystems in the evolution of the digital economy and sustainable development. The relevance of the study is due to the deployment of exponential technologies (artificial intelligence, the Internet of Things, cloud computing, etc.), which have caused and enabled the formation of digital ecosystems and will contribute to their spread. The purpose of the article is to define the essential features of digital ecosystems as a modern form of business and their role in transforming the business landscape in line with the current challenges of the digital economy. The methodology for studying business ecosystems is based on the key theoretical concepts that formed the basis for their formation, namely: the theory of complex systems, the theory of firm behaviour in quasi-competitive markets, and the theory of competitive co-operation. The methodological basis for the study of the ecosystem business model includes the theory of e-network economy, which focuses on horizontal relationships and spillover effects, and platform theory, which considers the interaction of participants in the process of creating common value. Results. It has been determined that business ecosystems contribute to the creation of a higher level of shared value than participants can obtain individually. The experience of the world's leading international companies shows that their strengthening and growth is driven by the use of an ecosystem model built on digital platforms, services and solutions. Global leaders of the digital economy (Apple, Amazon, Google, etc.) are examples of large digital ecosystems based on the integration of products, services, platforms and partnerships, which ensures their sustainability and ability to adapt to changes. The presence of communities of software developers, service providers, venture capitalists, startups and other participants in ecosystems is important for creating innovations and maintaining competitiveness in the long term. It has been proven that the implementation of ethical and environmental practices is a means of reducing risks and improving the reputation and viability of companies in the current environment. Business ecosystems can mitigate the negative effects of technological growth. Practical implications. It is proved that digital ecosystems play a key role in the development of the circular economy, which is a tool for achieving ESG. The authors identify the imperative directions of influence of digital ecosystems on the expansion of the circular economy. Value/Originality. The following has been further developed: the theory of business models through the definition of the essential features of digital ecosystems; the role of business ecosystems in improving the ESG criterion. Future research could be aimed at studying the institutional support for the development of business ecosystems at the international and national levels.